Principles and Practice of Urooncology Radiotherapy, Surgery and Systemic Therapy - Ozyigit, Gokhan; Selek, Ugur.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This evidence-based, state of the art guide to the management of urological malignancies, including bladder cancer, prostate cancer, and testicular cancer, is designed to serve as an easy-to-consult reference that will assist in daily decision making and the delivery of optimal care for individual patients within a multidisciplinary setting. Readers will find up-to-date information on patient selection and the full range of treatment modalities, including modern radiotherapy techniques, systemic chemotherapy, surgical procedures (including robotic surgery and other minimally invasive approaches), hormonal therapies, immunotherapy, and focal therapies. With regard to radiotherapy, the coverage encompasses everything from delineation of tumor volumes and organs at risk based on CT simulation through to delivery of stereotactic body radiotherapy, intensity-modulated radiation therapy, tomotherapy, volumetric modulated arc therapy, and proton therapy. The authors are leading authorities with international reputations who have been selected for their expertise in the topic that they address. The book will be of value for all practicing urooncologists as well as other oncology fellows and residents interested in urooncology.
Selection criteria based on Radiation Oncology perspective for definitive treatment approaches in urological cancers -- Radiological imaging in urological cancers -- The role of functional imaging in urological cancers -- Surgery in renal cell cancer -- Systemic therapies in renal cell cancer -- The role of radiotherapy in renal cell cancer -- Screening of prostate cancer: Pros and Cons -- Risk groupings in prostate cancer -- Active surveillance in low risk cancer: Pros and Cons -- Alternative focal therapies in low-risk prostate cancer: HiFU and Cryotherapy -- Robotic surgery in prostate cancer -- Radical retropubic prostatectomy in low-high risk prostate cancer -- Guidelines for the delineation of primary tumor target volume in prostate cancer -- Guidelines for the delineation of lymphatic target volumes in prostate cancer -- Modern radiotherapy techniques in prostate cancers -- Protontherapy for prostate cancer -- Brachytherapy for prostate cancer -- Stereotactic body radiotherapy for prostate cancer -- The role of hormonal therapies and radiotherapy in prostate cancer -- The role of hormonal therapies after surgery -- PSA after radiotherapy: Biochemical failure and PSA bounce -- Adjuvant and Salvage Radiotherapy in prostate cancer -- Reirradiation in prostate cancer -- Systemic chemotherapies in the management of prostate cancer -- Translational research and immunotherapy in prostate cancer -- Surgery in superficial and invasive bladder cancer -- Target volume delineation guidelines in bladder cancer -- Bladder preservation therapies in bladder cancer -- Systemic chemotherapies in bladder cancers -- Translational research and immunotherapy in bladder cancer -- Radiolabelled targeted therapies in urological tumors -- Radiation induced toxicity and related management strategies on urological malignancies -- Quality assurance of modern radiotherapy techniques in urological malignancies.
Keywords: Medicine; Radiotherapy; Oncology; Urology; Medicine & Public Health; Radiotherapy; Oncology; Urology